Evaluation of Generation Z’s Interest in Medan City in Choosing Study Programs and Careers in the Sharia Insurance Sector - Muzkiati Muzkiati; Aqwa Naser Daulay; Tri Inda Fadhila Rahma (Research Horizon, 2026)
The rapid growth of the Islamic financial industry has increased the demand for graduates with competencies in Sharia Insurance. However, Generation Z’s interest in choosing the Islamic Insurance Study Program and pursuing careers in the sector remains relatively limited. This study aimed to explore how Generation Z’s interest develops and identify the factors influencing their educational and career decisions through the perspective of the Theory of Planned Behavior. An exploratory qualitative approach was employed using focus group discussions involving fifteen participants selected through purposive sampling, consisting of prospective students, current students, and fresh graduates of the Islamic Insurance Study Program. Data were analyzed using thematic analysis through data reduction, coding, categorization, and theme development. The findings reveal that interest develops progressively across three stages: awareness, study-to-career transition, and career realization. At the awareness stage, educational interest is influenced by literacy, information exposure, and career perceptions. During university, practical learning experiences, competency development, and career exploration shape students’ career interests, while among graduates, career realization is characterized by adaptability and flexible career orientations. The findings indicate attitudes, subjective norms, and perceived behavioral control interact dynamically in influencing educational and career decisions.